FORCIBLE DIVERSION OF CIVIL AIRCRAFT UNDER INTERNATIONAL LAW (CASE STUDY OF RYANAIR FLIGHT 4978 IN BELARUS) - Faradita, Azahra Nafilah; Rosmawati, Rosmawati (Student Journal of International Law, 2022)
Every state has complete and exclusive sovereignty over the airspace above its territory under Article 1 of the 1944 Chicago Convention, Belarus carried out a forcible diversion of Ryanair Flight 4978 for the purpose of arresting a journalist and a pro-opposition activist from that country under this Article. However, forcible diversion of aircraft is also a form of hijacking and is contrary to Article 11 paragraph (1) of the 1963 Tokyo Convention and Article 1 of the 1970 Hague Convention. As a result, the international community has various reactions and opinions in an attempt to categorize the Belarusian act. This paper examines the international legal instruments related to the forcible diversion of civil aircraft as part of hijacking, the responsibility of the Belarusian Government, and legal settlement regarding the actions committed by Belarus. This paper found, Belarusian government actions are not categorized within the scope of the definition of hijacking regulated in the 1963 Tokyo Convention, the 1970 Hague Convention, and UNCLOS 1982.